A 2.4 GHz CMOS tunable image-rejection low-noise amplifier with active inductor - A'ain, Abu Khari; Ler, Chun Lee; Kordesch, Albert Victor (2006)

(untitled)
A 2.4-GHz CMOS fully-integrated tunable image-rejection (IR) low-noise amplifier (LNA) has been designed using Silterra's standard 0.18-Âµm CMOS process. The IR notch filter is designed using active inductor without using any passive inductor. With an image frequency of 1.34-GHz, post layout simulation results show the proposed IR LNA exhibits S21 of 27dB, S11 of-23.5dB, 2.2dB noise figure (NF) and input 1-dB compression point of-26dBm at 2.4-GHz. The IR of the IR LNA is -28dB and the tuning range for the IR notch filter is from 1.08 to 1.14-GHz. The first-stage of IR LNA dissipates not more than 10mw, including biasing circuit. The die area occupied by IR LNA is 0.49 mm2, excluding GSG pads